Economic Models for R and D Project Selection in the Presence of Project Interactions - Fox, G. Edward; Baker, Norman R.; Bryant, John L. (Management Science, 1984)
One reason existing approaches for dealing with benefit interactions in economic R and D project selection models are difficult to apply is that it is difficult to assess the interactions directly. This difficulty can be traced at least in part to the lack of a modeling framework within which different types of interaction can be identified and related to project and portfolio benefit. In this paper, a modeling framework is proposed within which certain kinds of benefit interactions, called present value (PV) interactions, are assessed indirectly by explicitly modeling R and D project impacts on profitability. Within the proposed framework, the role of traditionally recognized types of interaction in the calculation of present value is clarified, and it is shown that PV interaction exists even when traditionally recognized types of interaction are assumed to be absent. The proposed framework offers one method for assessing PV interactions. An example illustrates the framework and shows that ignoring PV interactions can result in both nonoptimal project selections and resource allocations, even when traditionally recognized types of interactions are absent. The framework and resulting model should be useful in enhancing decision making in firms using PV-based approaches to project selection, whether or not they are interested in using a model that accounts for PV interactions. This is expected since the overall framework provides a basis for analyzing the probable consequences of assuming that no PV interaction is present and for communicating these probable consequences to management